Analyzing the complex properties of bank account transaction network - Fang LYU; Xinlin ZHANG; Wei WANG; Junheng HUANG; Bailing WANG (网络与信息安全学报)
Firstly,a general directed and weighted transaction network model is built on the basis of the transaction characteristics of bank accounts.Secondly,referring to the definition of complex network,the complex network properties of the transaction network are verified from two levels of network structure and node.The network structure properties includes static properties,named scale-free property and small-world property,and dynamic evolution property,that is self-organization property.In addition,the attractor property is utilized for verifying the dynamical characteristic of complex network nodes.Finally,on the real bank account transaction data contains illegal pyramid marketing activities,the following conclusions were drawn:the network has scale-free property,small-word property,partially self-organization property and strange attractors.